1991
DOI: 10.1111/j.1476-5381.1991.tb12486.x
|View full text |Cite
|
Sign up to set email alerts
|

Salmeterol, a novel, long‐acting β2‐adrenoceptor agonist: characterization of pharmacological activity in vitro and in vivo

Abstract: 1 Salmeterol, a novel, long-acting /J-adrenoceptor agonist, has been compared with isoprenaline and salbutamol for activity in vitro on a range of f-adrenoceptor containing preparations from laboratory animals and man, and in vivo for bronchodilator activity in the conscious guinea-pig. 2 Salmeterol, like isoprenaline and salbutamol, relaxed preparations of both guinea-pig trachea (contracted by prostaglandin (PG)F2. or electrical stimulation) and human bronchus (contracted by PGF2a) in a concentration-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
96
1
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(110 citation statements)
references
References 11 publications
11
96
1
2
Order By: Relevance
“…There was a trend toward higher selectivity for abediterol and salmeterol than for formoterol and indacaterol; the comparison between abediterol and salmeterol selectivity ratios was difficult because of the low ␤ 1 efficacy observed for both compounds in guinea pig atria. Our results are consistent with those reported previously, indicating that the ␤ 1 /␤ 2 and ␤ 3 /␤ 2 selectivity ratios of formoterol and indacaterol are inferior to those of salmeterol (Ball et al, 1991;Battram et al, 2006;Bouyssou et al, 2010). In humans, it has been reported that activity at the ␤ 1 -adrenoceptor might be responsible for some of the cardiac side effects associated with ␤-adrenergic agonism (Levine and Leenen, 1989).…”
Section: Discussionsupporting
confidence: 83%
“…There was a trend toward higher selectivity for abediterol and salmeterol than for formoterol and indacaterol; the comparison between abediterol and salmeterol selectivity ratios was difficult because of the low ␤ 1 efficacy observed for both compounds in guinea pig atria. Our results are consistent with those reported previously, indicating that the ␤ 1 /␤ 2 and ␤ 3 /␤ 2 selectivity ratios of formoterol and indacaterol are inferior to those of salmeterol (Ball et al, 1991;Battram et al, 2006;Bouyssou et al, 2010). In humans, it has been reported that activity at the ␤ 1 -adrenoceptor might be responsible for some of the cardiac side effects associated with ␤-adrenergic agonism (Levine and Leenen, 1989).…”
Section: Discussionsupporting
confidence: 83%
“…Interestingly, the strips relaxed again very soon after removal of the antagonist. However, this recovery, which is denoted 'reassertion', occurs repeatedly after successive challenges with the antagonist [28][29][30]. Although other interpretations have also been suggested [25] (see also below), the diffusion Figure 1 'Microkinetic' model.…”
Section: Drug Partitioningmentioning
confidence: 99%
“…Sal has a long duration of action at the b2-AR that persists extensive washout of antagonist (Ball et al, 1991;Green et al, 1996). Therefore, it seemed plausible that Iso and Sal could differ in the duration of gene expression upregulation.…”
Section: Pronounced Differences In Upstream Cellularmentioning
confidence: 99%